Improving post harvest quality of custard apple using modified atmospheric packaging and storage temperature (Indian Journal of Arid Horticulture, 2016)
Investigation on 'Effect of modified atmospheric packaging and storage temperature on shelf life of custard applecv. Balanagar' was carried out with 14 treatment combinations. The uniform sized fully matured fruits of custard apple cv.Balanagar at colour turning stage were packed in medium density polyethylene bags (50μ density) with mixture of differentgaseous composition and stored in different storage temperatures. Two concentration of 0 2 (5% and 10% ), threeconcentration of CO2 (10%, 15% and 20%) and one control (environmental gaseous composition with 21% 0 2 and 0.03%CO2) were used in packages. Fruits were stored at ambient and 12°C temperatures. Higher TSS and total sugar, retention ofascorbic acid, acidity, phenols and highest scores for overall organoleptic attributes were found in low concentration of 0 2and CO2 in MAP and low temperatures storage. Finally this study indicated that custard apple fruit could be stored at l2°C for10 days with MAP (5% 02 and 10% CO2) allowed conservation of fruits with highest quality parameters. It also indicate thatstored custard apple fruit can be marketed for extended period and used for making various products.
Keywords: Modified atmosphere packaging; storage temperature; shelf life